Statistical modeling of social risk factors for sexually transmitted diseases among female youths in Nigeria (2013)
Introduction: Sexually transmitted diseases (STDs) are preventable, but the social risks factors connected to them are often not understood, particularly by female youths. There has been a dearth of information on the identification of social risk factors influencing STDs among female youths in Nigeria, hence we conducted this study. Methodology: This retrospective cross-sectional study utilized the Nigeria Demographic and Health Survey, 2008. It focused on female youths aged 15-24 (n=7,736) who ever had sexual intercourse. Data was analyzed using Chi-square and logistic regression models. Results: The mean age of the respondents was 20.2±2.5years. More female youths aged between 20 and 24 years contracted STDs in the last 12 months (2.5%) than those between the ages of 15 and 19 months (1.4%). A year prevalence of STDs among female youths in Nigeria was 2.1%. Socio-demographic factors such as age, education, wealth index, marital status, shared toilet, residence, contraceptive use, and total life-time number of sexual partners were found to be associated risk factors for contracting STDs (p<0.05). Controlling for potential confounding variables at the fifth iteration, the identified predictors of contracting STDs were wealth index, total lifetime number of sexual partners, awareness of HIV/AIDS, and shared toilet facility (p<0.05). Conclusions: The data confirmed the considerable impact of wealth index and awareness of HIV/AIDS as important predictors of STDs acquisition. Providing free condoms, along with teaching the importance of abstinence and improving knowledge of HIV/AIDS, can help to reduce the risk of STDs transmission.